Effect of polymer on disproportionate permeability reduction to gas and water for fractured shales. (1st March 2015) - Song, Zhaojie; Liu, Lingbo; Wei, Mingzhen; Bai, Baojun; Hou, Jirui; Li, Zhiping; Hu, Yunpeng
Highlights: Six shale fracture models with different fracture widths were fabricated. A method by which to calculate the residual resistance factor for gas was defined. Polymer can selectively reduce the permeability to water more than to gas. The F rr, water and F rr, gas tended to decrease as the fracture width grew. Polymer treatment does not impair gas flow, and may even improve it. Abstract: Large volumes of fracturing fluid are required in shale slickwater fracs, and a considerable amount of polymer friction reducer would remain in microfractures if the polymer has not been broken before gas production. It is of major interest to evaluate the effect of polymer on water/gas flow behavior in the microfractures of shale reservoirs. We fabricated six shale fracture models with different fracture widths and set up a core flooding apparatus to conduct brine/gas-injection experiments before and after polymer treatment. A method by which to calculate the residual resistance factor for gas ( F rr, gas ) was defined. The experimental results illustrate that polymer can reduce the permeability to water more than to gas. In the first cycle of brine/gas injection experiments after polymer treatment, the residual resistance factor for brine ( F rr, water ) and F rr, gas exhibited power-law characteristics through their shear rate and superficial gas velocity, respectively. The F rr, water and F rr, gas tended to decrease as the fracture width grew. Surprisingly, polymer treatment does not impair gas flow in wider fractures, and may even improve it. The mechanisms responsible for disproportionate permeability reduction (DPR) in the fractured shales were proposed in this paper.